Growth response of mixed mediterranean oak coppices to rainfall reduction - Cotillas, Miriam; Sabaté, Santi; Gracia, Carlos; Espelta, Josep Mª (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios
Keywords: climate change; Drought; Forest management; Quercus cerrioides; Quercus ilex; resprouting

Growth response of mixed mediterranean oak coppices to rainfall reduction (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios